2010
DOI: 10.1038/ajh.2010.38
|View full text |Cite
|
Sign up to set email alerts
|

Association of Osteoprotegerin With Aortic Stiffness in Patients With Symptomatic Peripheral Artery Disease and in Healthy Subjects

Abstract: The independent association between OPG and aPWV in patients with PAD and in controls suggests that the calcification inhibitor OPG may influence aortic stiffening in atherosclerosis and in clinically healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 23 publications
2
22
1
5
Order By: Relevance
“…Our findings are consistent with other human studies that have demonstrated associations between higher serum OPG levels and various adverse cardiovascular outcomes (14,15,17,20,31,32). These findings in humans are in contrast to studies in OPG-deficient mice who exhibit diffuse medial calcification of the aorta and renal arteries because of low OPG levels (6).…”
Section: Discussioncontrasting
confidence: 54%
“…Our findings are consistent with other human studies that have demonstrated associations between higher serum OPG levels and various adverse cardiovascular outcomes (14,15,17,20,31,32). These findings in humans are in contrast to studies in OPG-deficient mice who exhibit diffuse medial calcification of the aorta and renal arteries because of low OPG levels (6).…”
Section: Discussioncontrasting
confidence: 54%
“…Serum OPG levels and PWV were found to be significantly higher in diabetic patients than in the normoglycaemic group, and there is a significant association between serum OPG with inflammation and arterial stiffness [14]. Although other authors manifest that serum levels of OPG were not correlated to PWV [102], Zagura et al [103] indicated that the independent association between OPG and PWV observed in patients with peripheral artery disease (PAD) and in controls suggests that the calcification inhibitor OPG may influence aortic stiffening in atherosclerosis and in clinically healthy subjects. Taking together all these findings, we therefore conclude that increased OPG plasma levels observed during diabetes may favour the development of endothelial dysfunction in these patients.…”
Section: Opg and Endothelial Dysfunction In Diabetesmentioning
confidence: 98%
“…The OPN is an important inhibitor of vascular calcification. 21 As PAD is associated with vascular calcification, 22,23 it might be that increased serum OPN represents a compensatory mechanism aiming to inhibit progression of vascular calcification. However, further experimental studies are needed to determine the exact role of OPN in arterial stiffening.…”
Section: Discussionmentioning
confidence: 99%